Informal Teacher Leaders: Who They Are, What They Do, and How They Impact Teaching and Learning. Issue 6 (November 2021) - Gordon, Stephen P.; Jacobs, Jennifer; Croteau, Susan M.; Solis, Rachel
Educators in PK–12 schools were surveyed to seek their perceptions of colleagues who they considered informal teacher leaders, defined as leaders who were not appointed to a leadership role by a school or district administrator. The survey asked administrators, educational specialists, and teachers working in PK–12 schools across four states to share their perceptions of informal teacher leaders' leadership activities, personal and professional attributes, relationships with other educators, and impact. Open, axial, and selective coding were used to analyze the respondents' open-ended survey responses, and themes were developed relative to research topics. The respondents reported that the informal teacher leaders they identified engaged in important leadership activities at the individual, team, and school levels. The informal teacher leaders were described by respondents as passionate, caring, efficient, open to others, and professional. A variety of specific types of leadership knowledge and skills were attributed to the informal teacher leaders. Relationships of the informal teacher leaders with other educators were characterized as respectful, trusting, and warm, and the informal leaders' working relationships with other teachers and school administrators were considered positive. The respondents reported a variety of positive impacts of informal teacher leaders on students, teachers, and the school. Although many of the leadership activities, attributes, relationships, and impacts of informal teacher leaders parallel those of formal teacher leaders, a number of distinctions also were identified indicating some differentiation of roles and functions. Recommendations are made for educator programs, principals, and future research.